Self-Assembled Monolayers of Molecular Conductors with Terpyridine-Metal Redox Switching Elements: A Combined AFM, STM and Electrochemical Study - Kocábová, Jana; Vavrek, František; Nováková Lachmanová, Štěpánka; Šebera, Jakub; Valášek, Michal; Hromadová, Magdaléna (Molecules (Basel, Switzerland), 2022)
Self-assembled monolayers (SAMs) of terpyridine-based transition metal (ruthenium and osmium) complexes, anchored to gold substrate via tripodal anchoring groups, have been investigated as possible redox switching elements for molecular electronics. An electrochemical study was complemented by atomic force microscopy (AFM) and scanning tunneling microscopy (STM) methods. STM was used for determination of the SAM conductance values, and computation of the attenuation factor β from tunneling current-distance curves. We have shown that SAMs of Os-tripod molecules contain larger adlayer structures compared with SAMs of Ru-tripod molecules, which are characterized by a large number of almost evenly distributed small islands. Furthermore, upon cyclic voltammetric experimentation, Os-tripod films rearrange to form a smaller number of even larger islands, reminiscent of the Ostwald ripening process. Os-tripod SAMs displayed a higher surface concentration of molecules and lower conductance compared with Ru-tripod SAMs. The attenuation factor of Os-tripod films changed dramatically, upon electrochemical cycling, to a higher value. These observations are in accordance with previously reported electron transfer kinetics studies.
Keywords: rastrovací tunelová mikroskopie; AFM; STM; mikroskopie atomárních sil; oxidace-redukce; povrchové vlastnosti; self-assembled monolayer; electron transfer; Gold; Oxidation-Reduction; zlato; Microscopy, Atomic Force; redox switching; Microscopy, Scanning Tunneling; Surface Properties